Танкист, или "Белый тигр": роман / Илья Бояшов - Бояшов Илья Владимирович (Лимбус Пресс, 2008)
Экземпляры: ЦБ/3/6 (20100212) / Инвентарный номер: 45657 / Цена: 108.35 / Сис.шифр: Р2 / Авт.знак: Б 86 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6